Bilayered composite restoration: the effect of layer thickness on fracture behavior - Lippo Lassila; Eija Säilynoja; Roosa Prinssi; Pekka K. Vallittu; Sufyan Garoushi (United Kingdom, 2022)
Purpose: By combining the increased toughness of a resin composite reinforced with discontinuous fibers and the surface wear resistance of a particulate filler composite (PFC), a bilayered composite technique was recently introduced. This study aimed to evaluate the effect of the thickness of the overlaying PFC placed over a fiber-reinforced composite (FRC) core, on the fracture-behavior of direct crown restorations.
Methods: Six groups of posterior crown restorations (n=8/group) were fabricated having a discontinuous FRC-core (everX Flow) and a layer of surface PFC (Essentia U) with various thicknesses (0.5, 1.0, 1.5, 2.0 mm), with the remaining thickness of the bilayered being 6 mm.  Control groups were only made of PFC or FRC materials. Restorations were statically loaded until fracture. Failure-modes were visually examined. Data were analyzed using ANOVA (p = 0.05) and regression analysis.
Results: The regression analysis showed that by decreasing the thickness of PFC layer, the load bearing capacity of restorations increased linearly (R2=0.7909). ANOVA revealed that crown restorations made only from everX Flow composite had significantly higher load-bearing capacities (3990 ±331 N) (p<0.05) among all the groups tested. With regard to the failure-mode analysis, crowns that had a FRC core material of everX Flow revealed delamination of the PFC surface composite from the core. Crowns which were made only of PFC i.e. with no fiber reinforcement, showed a crushing-like fracture pattern.
Conclusions: Restorations combining a thick FRC-core and a thin surface layer of PFC (0.5-1 mm), displayed promising performance related to fracture-behavior and load-bearing capacity.